EFFECT OF ADDITIONAL GRIP ON TENSILE STRENGTH OF NON-FERROUS MATERIALS FOR SHIP - Setyawan, Dony; Sulisetyono, Aries; Aryawan, Wasis Dwi (Journal of Applied Engineering Science, 2022)
Non-ferrous material frequently slipped failure, hard clamp surface press slip occurs, and non-metal material lacks a rigidity hold for the clamp, resulting in a slip or break before the limit strength. So as efforts to prevent this problem are carried out from additional grips to reduce the occurrence of slips to obtain an increased testing accuracy. Additional grip designs are created using material sizes specified by ASTM D638. material grip receives pressure equal to 106.4 MPa, so to prevent deformation, stainless material is chosen as additional grip. This test is to determine the quality of the materials used for the ship. In this research, a test using additional grip was developed to improve technology for the test. Continued data analysis and a conclusion were obtained that the tensile test using tools has a high success rate. Rubber and fibre-reinforced plastic (FRP) specimens have a success rate of 60%. The factor causing the low success rate of wood testing is that the wood fibres have an irregular direction, so this uncertainty makes the tensile test results unsuccessful. From the tensile testing process, the ultimate stress value of specimens without grip tools is lower than tests with additional grips. The ultimate stress rubber value was 51.92%, the FRP was 16.40% more than the ultimate stress with the average value, and moreover, the tensile strength of HDPE also elongated as accepted by the rules.